Membrane contact reactors for three-phase catalytic reactions - Wales, Michael Dean (Kansas State University, 2016)
Membrane contact reactors (MCRs) have been evaluated for the selective hydro-treating of model reactions; the partial hydrogenation of soybean oil (PHSO), and the conversion of lactic acid into commodity chemicals. Membranes were rendered catalytically active by depositing metal catalyst onto the polymer "skin" of an asymmetric membrane. Hydrogen was supplied to the support side of the membrane and permeated from the support side to the skin side, where it adsorbed directly onto the metal surface. Liquid reactant was circulated over the membrane, allowing the liquid to come into direct contact with the metal coated surface of the membrane, where the reaction occurred. Our membrane contact reactor approach replaces traditional three-phase batch slurry reactors. These traditional reactors possess inherent mass transfer limitations due to low hydrogen solubility in liquid and slow diffusion to the catalyst surface. This causes hydrogen starvation at the catalyst surface, resulting in undesirable side reactions and/or extreme operating pressures of 100 atmospheres or more. By using membrane reactors, we were able to rapidly supply hydrogen to the catalyst surface. When the PHSO is performed in a traditional slurry reactor, the aforementioned hydrogen starvation leads to a high amounts of trans-fats. Using a MCR, we were able to reduce trans-fats by over 50% for equal levels of hydrogenation. It was further demonstrated that an increase in temperature had minimal effects on trans-fat formation, while significantly increasing hydrogenation rates; allowing the system to capture higher reaction rates without adversely affecting product quality. Additionally, high temperatures favors the hydrogenation of polyenes over monoenes, leading to low amounts of saturated fats. MCRs were shown to operator at high temperatures and: (1) capture high reaction rates, (2) minimize saturated fats, and (3) minimize trans-fats. We also demonstrated lactic acid conversion into commodity chemicals using MCRs. Our results show that all MCR experiments had faster reaction rate than all of our controls, indicating that MCRs have high levels of hydrogen coverage at the catalyst. It was also demonstrated that changing reaction conditions (pressure and temperature) changed the product selectivities; giving the potential for MCRs to manipulate product selectivity.
Keywords: Membrane reactor; Three-phase reactions; Catalyst; Partial hydrogenation of soybean oil; Lactic acid; Mass transfer resistance; Chemical Engineering (0542); Materials Science (0794); Polymer Chemistry (0495)